2021
DOI: 10.3389/fsufs.2021.723301
|View full text |Cite
|
Sign up to set email alerts
|

Poverty Alleviation Through Technology-Driven Increases in Crop Production by Smallholder Farmers in Dryland Areas of Sub-Saharan Africa: How Plausible Is This Theory of Change?

Abstract: The current paradigm of agricultural research and extension in support of rural development in Sub-Saharan Africa (SSA) is to disseminate improved technologies designed to increase the generally low crop yields per hectare on individual farms. Using data from a baseline survey (n = 7,539) from a large rural development programme implemented in five countries in SSA, we calculate the increases in yield per hectare required to significantly contribute to poverty alleviation for households managing such farms. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Female adults made the day-to-day management decisions of the farm with great reliance on the local NGO for long-term planning. The active involvement of the NGO was appreciated and reported by the households to have far greater positive impacts than government departments and their programs, something also previously observed (Hebinck et al, 2011;Naumann, 2014;de la Hey and Beinart, 2017;Harris et al, 2021).…”
Section: Diversity Of Small-scale Farming Systemsmentioning
confidence: 55%
“…Female adults made the day-to-day management decisions of the farm with great reliance on the local NGO for long-term planning. The active involvement of the NGO was appreciated and reported by the households to have far greater positive impacts than government departments and their programs, something also previously observed (Hebinck et al, 2011;Naumann, 2014;de la Hey and Beinart, 2017;Harris et al, 2021).…”
Section: Diversity Of Small-scale Farming Systemsmentioning
confidence: 55%
“…We also considered remittances, but they were just minor. Similarly, a recent study by Harris et al (2021), conducted in five African countries (Mali, Niger, Ethiopia, Burkina Faso and Kenya), found that the productivity is not sufficient to reach the poverty line ($1.90 per capita and day).…”
Section: Food Security and Povertymentioning
confidence: 94%
“…Dairy production has the potential to diversify smallholder agriculture and bolster income (Banda et al, 2021;Chagunda et al, 2016). This is especially in contexts where land holdings are too small to make crop production alone economically viable (Harris et al, 2021). Yet, there are multiple issues that affect the realization of this potential.…”
Section: Introductionmentioning
confidence: 99%